13 steps to bloody good luck - Ashwin Sanghi (Chennai : Westland, 2014)
Through engaging anecdotes, personal stories, and bits of homespun wisdom, Ashwin offers a fresh perspective on how individuals can cultivate their own luck.
Keywords: Attitudes; Chance; Fortune; Life; Motivation; Philosophy